2022
DOI: 10.1042/bcj20220051
|View full text |Cite
|
Sign up to set email alerts
|

Activation and manipulation of inflammasomes and pyroptosis during bacterial infections

Abstract: Following detection of pathogen infection and disrupted cellular homeostasis, cells can activate a range of cell death pathways, such as apoptosis, necroptosis and pyroptosis, as part of their defence strategy. The initiation of pro-inflammatory, lytic pyroptosis is controlled by inflammasomes, which respond to a range of cellular perturbations. As is true for many host defence pathways, pathogens have evolved multiple mechanisms to subvert this pathway, many of which have only recently been described. Herein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 151 publications
0
6
0
Order By: Relevance
“…Pathogen‐triggered cell death has important consequences on sepsis progression. [ 7 , 12 ] We first determined the occurrence of apoptosis of host cells in response to Staphylococcus aureus ( S. aureus ) infection. Since bacterial components trigger apoptosis in macrophages during an innate defense process, [ 13 ] we evaluated apoptosis of macrophages in a S. aureus infection model ( Figure 1 a ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pathogen‐triggered cell death has important consequences on sepsis progression. [ 7 , 12 ] We first determined the occurrence of apoptosis of host cells in response to Staphylococcus aureus ( S. aureus ) infection. Since bacterial components trigger apoptosis in macrophages during an innate defense process, [ 13 ] we evaluated apoptosis of macrophages in a S. aureus infection model ( Figure 1 a ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that host uses programmed immune cell death to fight infections. [ 7 , 15 ] Given that we found the production of apoEVs is a feature of host response to infection, we evaluated the therapeutic potential of apoEVs and tested their effects on S. aureus ‐induced sepsis model. ApoEVs derived from in vitro cultured apoptotic BMDMs were intravenously administered after disease onset (Figure 2i ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mature IL-18 and IL-1β are secreted from the membrane pores to the cellular exterior and gather vast quantities of the inflammatory cells outside the cell to expand the inflammatory response. [12][13][14][15][16][17] The nonclassic pyrolysis pathway is mainly directly recognized by caspase-4/5/11 and combined with the endotoxin lipopolysaccharide of gram-negative bacteria. After being activated by oligomerization, it shows the corresponding protease activity.…”
Section: Discussionmentioning
confidence: 99%
“…Genes associated with these diseases have been sequentially identified since 1997 onwards, and with the exception of MKD, the majority of them encode for proteins involved in the inflammasome architecture or in programmed cell death [ 11 ]. In particular, inflammasomes, structured with a central sensor protein, an adaptor protein and CASPASE-1, modulate IL-1β release and work as platforms to protect the human body from the outnumber of pathogenic organisms [ 12 ].…”
Section: Prelude To the Concept Of Autoinflammationmentioning
confidence: 99%